Formal [4+1] Cycloaddition of o‐Aminobenzyl Chlorides with Isocyanides: Synthesis of 2‐Amino‐3‐Substituted Indoles. Issue 3 (19th February 2019) - Jong, Jacobus A. W.; Bao, Xu; Wang, Qian; Zhu, Jieping
Abstract: Reaction of substituted o ‐aminobenzyl chlorides with isocyanides in the presence of a weak base (NaHCO3 ) at room temperature afforded the diversely functionalized 2‐aminoindoles in good to excellent yields. A formal [4+1] cycloaddition of the in situ generated aza‐ ortho ‐xylylenes with isocyanides accounted for the reaction outcome. Abstract :